T cell immunotherapy for cervical cancer: challenges and opportunities - Yu, Lingfeng; Lanqing, Gong; Huang, Ziyu; Xin, Xiaoyan; Minglin, Liang; Fa-hui, Lv; Zou, Hongmei; Min, Jie (Frontiers in Immunology, 2023)
Cancer cellular immunotherapy has made inspiring therapeutic effects in clinical practices, which brings new hope for the cure of cervical cancer. CD8+T cells are the effective cytotoxic effector cells against cancer in antitumor immunity, and T cells-based immunotherapy plays a crucial role in cellular immunotherapy. Tumor infiltrated Lymphocytes (TIL), the natural T cells, is approved for cervical cancer immunotherapy, and Engineered T cells therapy also has impressive progress. T cells with natural or engineered tumor antigen binding sites (CAR-T, TCR-T) are expanded in vitro, and re-infused back into the patients to eradicate tumor cells. This review summarizes the preclinical research and clinical applications of T cell-based immunotherapy for cervical cancer, and the challenges for cervical cancer immunotherapy.